2012
DOI: 10.1186/1746-6148-8-37
|View full text |Cite
|
Sign up to set email alerts
|

One-step multiplex real time RT-PCR for the detection of bovine respiratory syncytial virus, bovine herpesvirus 1 and bovine parainfluenza virus 3

Abstract: BackgroundDetection of respiratory viruses in veterinary species has traditionally relied on virus detection by isolation or immunofluorescence and/or detection of circulating antibody using ELISA or serum neutralising antibody tests. Multiplex real time PCR is increasingly used to diagnose respiratory viruses in humans and has proved to be superior to traditional methods. Bovine respiratory disease (BRD) is one of the most common causes of morbidity and mortality in housed cattle and virus infections can play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
68
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 27 publications
3
68
0
2
Order By: Relevance
“…BRSV outbreaks most commonly occur in winter (Valarcher and Taylor 2007) and BRSV-related disease is highly dependent on animal age (Hagglund and others 2006). Studies by Thonur (Thonur and others 2012) reported single detections of BoHV1 (20 per cent), BRSV (10 per cent) and PI3 (3 per cent) in a subset of UK nasal calf swabs tested using multiplex RT-PCR. Forty-four percent of calves tested in a targeted Scottish study (Hotchkiss and others 2010) were positive for PI3 virus, with much lower levels (10 per cent) of BRSV detected while Pardon reported 60 and 20 per cent positive viral detections for BVDV and BRSV, respectively, in veal calves which died due to BRD (Pardon and others 2011).…”
Section: Discussionmentioning
confidence: 99%
“…BRSV outbreaks most commonly occur in winter (Valarcher and Taylor 2007) and BRSV-related disease is highly dependent on animal age (Hagglund and others 2006). Studies by Thonur (Thonur and others 2012) reported single detections of BoHV1 (20 per cent), BRSV (10 per cent) and PI3 (3 per cent) in a subset of UK nasal calf swabs tested using multiplex RT-PCR. Forty-four percent of calves tested in a targeted Scottish study (Hotchkiss and others 2010) were positive for PI3 virus, with much lower levels (10 per cent) of BRSV detected while Pardon reported 60 and 20 per cent positive viral detections for BVDV and BRSV, respectively, in veal calves which died due to BRD (Pardon and others 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability to perform ELISA within a short time frame to detect different viral agents reduces hands-on time in the laboratory, is more efficient in differential diagnosis [27]. In this study, the samples have no examined by FAT or isolation so there is not evaluated the specificity of other tests.…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made to develop a more effective diagnostic assay, including recent PCR approaches that can detect BPIV3 http://dx.doi.org/10.1016/j.jviromet.2015.05.015 0166-0934/© 2015 Elsevier B.V. All rights reserved. nucleic acids in clinical samples from cattle (Thonur et al, 2012). In general, serological assays, including indirect immunofluorescence assay (IF), serum neutralisation test (SNT), complement fixation (CF), hemagglutination inhibition (HI), and Enzyme-Linked Immunosorbent Assay (ELISA) have been frequently employed to detect BPIV3 infection (Adair, 1986;Key and Derbyshire, 1984;Trybala et al, 1989).…”
Section: Introductionmentioning
confidence: 98%